SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN DANA BOS UNTUK SEKOLAH DASAR DENGAN METODE AHP (DINAS PENDIDIKAN KEC. SEI KEPAYANG) - Novica Irawati; Hommy D.E Sinaga; Adyanata Lubis (RJOCS (Riau Journal of Computer Science), 2018)
Decision Making Application Acceptance BOS To Elementary School With AHP method. Has created a system as a tool for selecting beneficiary schools boss. In this system willhave primary schools are eligible to receive funding boss in the next year. The criteria used adalam this application are: Reports Tri Wulan, Dapodikmen Data, Indicators Improvement,Service, Student Achievement, Achievement Teacher, School Achievement and Accreditation. In this study, computational methods of decision-making system that is used is the Analytical Hierarchy Process (AHP). AHP settlement process are: a. Determine the order of priority criteria, b. Determining the value of the weight of each school, c. Shape calculated by AHP. The final result of the school priority value is used as decision-making tools